Investigating Consumer Demand and Willingness to Pay for Fresh, Local, Organic, and “On-the-Stalk” Edamame - Lord, Nick; Zhang, Bo; Neill, Clinton L. (Frontiers in Sustainable Food Systems, 2021)
Introduction of locally-adapted, commercially-viable edamame varieties can allow it to be marketed as fresh, local, organic, or on-the-stalk. Here, we utilized contingent valuation (CV) methodology to estimate mean WTP for these external attributes in relation to a vector of explanatory variables. Results showed 94, 88, and 33-cent premiums for fresh, local, and organic edamame. Pro-environmental attitudes drove WTP for all three of these attributes, while shopping locale significantly increased mean WTP for fresh and organic attributes. A 40-cent price discount was observed for the “on-the-stalk” attribute, suggesting that convenience also plays an important role in marketing edamame.